2016
DOI: 10.3390/e18010023
|View full text |Cite
|
Sign up to set email alerts
|

Long Range Dependence Prognostics for Bearing Vibration Intensity Chaotic Time Series

Abstract: According to the chaotic features and typical fractional order characteristics of the bearing vibration intensity time series, a forecasting approach based on long range dependence (LRD) is proposed. In order to reveal the internal chaotic properties, vibration intensity time series are reconstructed based on chaos theory in phase-space, the delay time is computed with C-C method and the optimal embedding dimension and saturated correlation dimension are calculated via the Grassberger-Procaccia (G-P) method, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…The detailed algorithm of EVI is given in our previous work [37]. Figure 8b reveals that the evolution of kurtosis can be divided into three stages, i.e., normal operation, incipient fault and severe fault stage.…”
Section: Case 1-results and Discussion Of Bearing Single Faultmentioning
confidence: 99%
“…The detailed algorithm of EVI is given in our previous work [37]. Figure 8b reveals that the evolution of kurtosis can be divided into three stages, i.e., normal operation, incipient fault and severe fault stage.…”
Section: Case 1-results and Discussion Of Bearing Single Faultmentioning
confidence: 99%
“…Therefore, the incipient fault diagnosis (IFD) and health management of rolling bearings are becoming more and more crucial in engineering applications [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…From the view of application, roughly, the existing prediction approaches can be divided into two categories: (a) parametric-based methods and (b) nonparametric-based methods. In the literature, parametric-based methods mainly include time-series methods such as autoregressive moving average (ARMA) [7,8], fractional autoregressive integrated moving average (FARIMA) [9,10], fractional Brownian motion (FBM) [11,12], hidden Markov model (HMM) [13,14] and grey theoretical model (GTM) [15,16], etc. Generally, the parametric-based methods overcome the hurdle of predictive availability during long-term prediction (according to needs) which assumes the model's parameters to be constants in the predicted region.…”
Section: Of 27mentioning
confidence: 99%
“…Figure 8 shows the peak-to-peak values of the whole lifetime of bearing 1. Accordingly, the health indicators, i.e., equivalent vibration intensity (EVI) [9,11], Kurtosis and EVI of bearing 2, bearing 3 and bearing 4 are illustrated in Figure 9a-c, respectively. It is seen that the amplitudes of bearings 1, 3 and 4 have gradual increasing trends, in addition, the whole test life of bearing 3 is the shortest due to harsh operating conditions, which indicates that the extremely failures are occurred before the experiment stops, thus, representing abrupt degradation processes, whereas the EVI amplitudes of bearings 2 show gradual increases; it might be concluded that the design/manufacturing quality and fatigue resistance strength are much higher than others under the same operating conditions.…”
Section: Experimental Validationsmentioning
confidence: 99%